Chronic Subdural Hematoma - A Dilemma to Put Drain (Bangladesh Journal of Neurosurgery, 2019)
Background: A chronic subdural hematoma (CSDH) is a collection of blood and blood breakdown products between the surface of the brain and its outermost covering the dura for more than 21 days. The elderly patients are more likely to develop a subdural hematoma, particularly from trivial trauma. CSDHs have been evacuated by burr holes, twist-drill craniotomies and craniotomies. The treatment of chronic subdural haematoma by burr hole drainage has been performed usually without using a closed drainage system, the problem of intracranial air entrapment still persists and can cause a deterioration in the level of consciousness or seizures in the postoperative period. We wanted to compare the effects of patient with drain and those without drain.Objectives: our study is to compare the clinical outcome of CSDH with or without drain.Methods: This prospective study was carried out at CMH Dhaka from January 2017 to July 2018; total 70 cases were investigated for the effectiveness of subdural drain. Cases were randomly allocated in two groups. Data were collected by specially designed questionnaire and analyzed by SPSS.Results and Observation: 70 patients of CSDH were included in this study out of which 25 underwent burr hole with closed system drainage and 45 underwent burr hole without closed system drainage. They were divided into Group A and B, respectively. Among the total number of patients 14 (20%) had shown recurrence. Out of 14 patients, 12 belong to Group B (86 %) and 2 belong to Group a (14 %).Conclusion: It is concluded that, those with a closed system drainage recurrence rate is significantly lower than with burr-hole evacuation alone.Bang. J Neurosurgery 2019; 9(1): 26-32